Strategi Repositioning Bisnis Multi Level Marketing dan Tinjauan Dari Prespektif Syariah - Cahyadi, Iwan Fahri (Universitas Islam Negeri Sunan Kudus, 2019)
In the last few years this business with the concept of multi level marketing is growing and thriving in Indonesia. In terms of positive law and legal religion, MLM business does not violate the rules. But early in the year 2019, MLM business again got the attention, namely the existence of recommendations of one of Indonesia's largest religious organization. In March 2019 in the closing of the National Congress of scholars conferences Nahdlatul Ulama (NU) at boarding schools Miftahul Huda Al-Azhar, Citangkolo, Banjar, West Java, that MLM business is unlawful. According to Marimin el al., (2016:7) in the journal entitled